Distinct spatial scale sensitivities for early categorization of faces and places: neuromagnetic and behavioral findings - Awasthi, Bhuvanesh; Sowman, Paul F.; Friedman, Jason; Williams, Mark A. (Frontiers in Human Neuroscience, 2013)
Research exploring the role of spatial frequencies in rapid stimulus detection and categorisation report flexible reliance on specific spatial frequency bands. Here, through a set of behavioural and magnetoencephalography (MEG) experiments, we investigated the role of low spatial frequency (LSF)(<8 cpf) and high spatial frequency (HSF)(>25 cpf) information during the categorisation of faces and places. Reaction time measures revealed significantly faster categorisation of faces driven by LSF information, while rapid categorisation of places was facilitated by HSF information. The MEG study showed significantly earlier latency of the M170 component for LSF faces compared to HSF faces. Moreover, the M170 amplitude was larger for LSF faces than for LSF places, whereas the reverse pattern was evident for HSF faces and places. These results suggest that spatial frequency modulates the processing of category specific information for faces and places.